Physical education and sports graduate’s professional independence diagnostics - Parfenova, A.M.; Sazonova, S.L.; Raskovalova, D.A.; Sazonov, N.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test the academic physical education and sports graduates’ professional independence. Methods and structure of the study. Professional independence may be defined as the individual concentration on the self-reliant professional service quality and efficiency ranked among the most important credentials critical for success in the professional service design, management and perfection domains; with this quality mastered and excelled by students largely in the self-education process so that to make them fully fit for the future professional service. The graduate's professional independence rating criteria may be listed as follows: sustainable motivations for persistent professional progress by a range of means dominated by self-education; diligence and efficiency in attaining every goal; ability to master best professional service models and tools and implement innovative physical education and sports technologies and practices; successfully cooperate with the relevant public, commercial and non-governmental organizations; design, manage and control teamwork in a capacity of a team leader and decision-maker; analyze the individual and corporate progresses; and revise own professional service when necessary. Every professional independence element may be scored in points indicative of the self-educational determination and professional competences. Results and conclusion. Modern physical education and sports specialist is expected to demonstrate high knowledge, skills, competences and individual creativity as drivers for continuous professional education, self-improvement and progress, for the physical education and sport specialist being able to effectively contribute to the progress of the physical education and sport service his/ her versatile skills and experience on the professional independence basis, with the professional independence ranked among the most valuable professional qualities.